Cover Picture: Catalytic Asymmetric Hydroalkenylation of Vinylarenes: Electronic Effects of Substrates and Chiral N‐Heterocyclic Carbene Ligands (Angew. Chem. Int. Ed. 15/2015). Issue 15 (24th March 2015) - Ho, Chun‐Yu; Chan, Chun‐Wa; He, Lisi
<x xml:space="preserve">Abstract</x> An asymmetric cross‐hydroalkenylation …︁ …︁ catalyzed by [NiH] complexes provides branched gem‐disubstituted olefins with high enantio‐ and chemoselectivity, depending on the steric and electronic effects of the substrates and N‐heterocyclic carbene (NHC) ligands. In their Communication on page 4512 ff., C.‐Y. Ho and co‐workers rule out a π–π stacking mechanism and suggest that the N‐aryl rings of the NHCs possibly "move like wings" to coordinate a π system with a NiII center.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>